Factors associated with spontaneous preterm birth in Addis Ababa public hospitals, Ethiopia: cross sectional study - Deressa, Ababe Tamirat (BMC Pregnancy Childbirth, 2018)
BACKGROUND: Spontaneous preterm birth is commencement of labor with intact or pre labor rapture of membrane and birth before 37 weeks of gestation. The aim of this study was to identify common factors associated with spontaneous preterm birth in Addis Ababa public hospitals. METHODS: After random selection of three hospitals from the six Addis Ababa’s Public hospitals having Neonatal intensive care unit, systematic sampling was employed to select study units from admission log book of the neonates. Data were collected using structured checklist. Finally, data entered to EpiData 3.1 and transported to SPSS 22 for analysis. Bivariate and multivariate logistic regression analysis was done for the variables. RESULT: The mean gestational age of preterm birth was 32.45 (±2.903 SD). Majority (66.1%) of preterm births were spontaneous and 33.9% were induced preterm births. Hypertension during pregnancy [P = 0.001, AOR = 0.182, 95% CI: (0.067, 0.493)] and maternal HIV infection [P = 0.041, AOR = 3.408 95% CI: (1.048, 11.079)] significantly associated with spontaneous preterm birth. CONCLUSION: Those mothers who were diagnosed with hypertension during pregnancy less likely gave spontaneous preterm birth than who had no history of hypertension during pregnancy and HIV positive mothers gave spontaneous preterm more likely than HIV negative mothers. Thus, giving emphasis to these factors with appropriate care during pregnancy is important to reduce spontaneous preterm birth.